Wabanaki Forests: Identity, Cultural Connections, and a Call for New Collaborations - Pawling, Micah (Maine Policy Review, 2025)
Author Micah A. Pawling explores Wabanaki people’s views on forest lands as part of their cultural identity. Wabanaki forests represent self-sufficiency and knowledge systems that many tribal citizens use to reinforce their identity as Indigenous people. These forests reveal that the repercussions of settler colonialism are complex and ever changing. Historical research shows that Wabanaki leaders have had to devise innovative solutions to solve challenges about their forest lands. Cross-cultural collaborations can produce powerful results in the overall health and expanse of Wabanaki forests, provided that non-Native partners embrace very different views of forest policy. Policymakers need to consider the significance of tribal forest history, specifically Wabanaki values about forest lands, to shape appropriate and effective decisions today.
Keywords: Penobscot; Passamaquoddy; Mi'kmaq; Maliseets; land back movement